2024
DOI: 10.1101/2024.02.20.581146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autonomic modulations to cardiac dynamics in response to affective touch: Differences between social touch and self-touch

Diego Candia-Rivera,
Rebecca Boehme,
Paula C. Salamone

Abstract: The autonomic nervous system plays a vital role in self-regulation and responding to environmental demands. Autonomic dynamics have been hypothesized to be involved in perceptual awareness and the physiological implementation of the first-person perspective. Based on this idea, we hypothesized that the autonomic activity measured from cardiac dynamics could differentiate between social touch and self-touch. In our study, we used a newly developed method to analyze the temporal dynamics of cardiac sympathetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The role of parasympathetic/vagal activity remains poorly understood, although many contexts revealed that affective touch activates the parasympathetic nervous system [50][51][52][53][54] . In our recent research, we showed that affective touch causes a decrease in cardiac sympathetic activity and an increase in cardiac parasympathetic activity, which was more pronounced in the case of social touch 29 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The role of parasympathetic/vagal activity remains poorly understood, although many contexts revealed that affective touch activates the parasympathetic nervous system [50][51][52][53][54] . In our recent research, we showed that affective touch causes a decrease in cardiac sympathetic activity and an increase in cardiac parasympathetic activity, which was more pronounced in the case of social touch 29 .…”
Section: Discussionmentioning
confidence: 88%
“…The protocol consisted in the recording of EEG and ECG data while undergoing three distinct conditions: social touch (being stroked on the forearm by the experimenter), self-touch (stroking of the participant's own forearm), and object-touch (participant stroking a pillow) as a control condition. Each of the three conditions lasted 180 seconds, that were analyzed in the segments 0-60, 60-120 and 120-180 seconds, as done previously 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dobutamine acts as a positive ionotropic, known as sympathomimetic [2]. In our proposed method, previously validated in humans [10,27], we accurately show the time-dependent effects of autonomic elicitation induced by dobutamine in rats, unraveling some of the key components of cardiac regulation by both sympathetic and parasympathetic systems. As expected, our results show that dobutamine triggers an increase in sympathetic activity, shown as a sudden increase in slow fluctuations in HRV, followed by a transient increase in the baseline heart rate.…”
Section: Discussionmentioning
confidence: 94%